Customer perception on service quality for Bayu Balau Beach Resort (hotel & chalet) / Mohammad Nur Asyraf Md Sahlan - Md Sahlan, Mohammad Nur Asyraf (2017)
Quality of service is intangible to understand and measure but it should have tool in measure the quality for service provider to understand what their customer want. Bayu Balau Beach Resort is mid-scale hotel that still finding that what their guest see through their product in measure their service. If we talk about full scale hotel and luxury hotel there is many thing to consider to measure their quality from the small thing to the bigger thing are all count for delight their guest. In other side, mid-scale hotel or resort is accommodation service provider that do not have all the luxury thing but still they provide a good service for their service. I as researcher want to understand what the factor that guest see through to the resort especially in Bayu Balau Beach Resort that can consider in measure the quality of the service. The factor that I have in this research is product service, product delivery, and product environment. Product service is about the tangible product it service such as room and facilities. While product delivery about human to human interaction (staff and guest). Lastly product environment is about the horizon of the place, the nature and what the geographic of the place offer for guest to enjoy such as fresh air, beach, uptown seeing and etc.